Influence of future air pollution mitigation strategies on total aerosol radiative forcing - Kloster, S; Dentener, F; Felchter, J; Raes, F; van Aardenne, J; Roeckner, E; Lohmann, U; Stier, P; Swart, R (Copernicus Publications, 2008)
We apply different aerosol and aerosol precursor emission scenarios reflecting possible future control strategies for air pollution in the ECHAM5-HAM model, and simulate the resulting effect on the Earth's radiation budget. We use two opposing future mitigation strategies for the year 2030: one in which emission reduction legislation decided in countries throughout the world are effectively implemented (current legislation; CLE 2030) and one in which all technical options for emissions reductions are being implemented independent of their cost (maximum feasible reduction; MFR 2030). We consider the direct, semi-direct and indirect radiative effects of aerosols. The total anthropogenic aerosol radiative forcing defined as the difference in the top-of-the-atmosphere radiation between 2000 and pre-industrial times amounts to -2.00 W/m². In the future this negative global annual mean aerosol radiative forcing will only slightly change (+0.02 W/m²) under the "current legislation" scenario. Regionally, the effects are much larger: e.g. over Eastern Europe radiative forcing would increase by +1.50 W/m² because of successful aerosol reduction policies, whereas over South Asia it would decrease by -1.10 W/m² because of further growth of emissions. A "maximum feasible reduction" of aerosols and their precursors would lead to an increase of the global annual mean aerosol radiative forcing by +1.13 W/m². Hence, in the latter case, the present day negative anthropogenic aerosol forcing could be more than halved by 2030 because of aerosol reduction policies and climate change thereafter will be to a larger extent be controlled by greenhouse gas emissions. We combined these two opposing future mitigation strategies for a number of experiments focusing on different sectors and regions. In addition, we performed sensitivity studies to estimate the importance of the aerosol microphysical coupling within the range of expected future changes. For changes in oxidant concentrations caused by future air pollution mitigationm we do not find a significant effect for the global annual mean radiative aerosol forcing. In the extreme case of only abating SO2 or carbonaceous emissions to a maximum feasible extent, we find deviations from additivity for the radiative forcing over anthropogenic source regions up to 10% compared to an experiment abating both at the same time.